HEALTH EDUCATION PRACTICE AS PERCEIVED BY SENIOR HIGH STUDENTS - Cícero Tavares Leite; Roberta Peixoto Vieira; Caroline Antero Machado; Glauberto da Silva Quirino; Maria de Fátima Antero Sousa Machado (Universidade Federal do Paraná, 2014)
This quantitative study was undertaken with 571 students aged between 14 and 19 years old from three state senior high schools, aiming to describe the students' perceptions regarding the practice of health education in the school. Data collection occurred following the acceptance of the adolescents and those legally responsible for them, between February and March 2012, through questionnaires with objective questions, organized using the Statistical Package for Social Sciences software, version 18.0, with data presented through description, frequency and in tables. The results indicated that (59%) recognized the existence of times of health education, addressing sexuality (61.5%), and alcohol and drugs (59.6%). According to those studied, (43%) asserted that there had been no qualified listening prior to the activities, (66%) did not recognize the participation of the Family Health Strategy, and 56% evaluated the pedagogical interventions as dissatisfactory. It is concluded that the Family Health Strategy must work alongside the adolescents so as to strengthen the bonds with this public.